Disentangling the simultaneous effects of habitat degradation and introduced species on naturally depauperate riverine fish communities - Meijer, Christopher G.; Hickford, Michael J. H.; Gray, Duncan P.; Schiel, David R. (Frontiers in Freshwater Science, 2024)
Global change is a multi-faceted issue that is putting many species at risk. The broad range of potentially interacting environmental stressors is problematic for effective and efficient conservation and management. In freshwater systems, habitat degradation and introduced species have been repeatedly recognised for their extensive impacts on native ecosystems. However, the simultaneous impacts of these environmental stressors on naturally depauperate and inherently vulnerable communities are poorly understood. Working in southern New Zealand, the fish communities in 14 tributaries of three lowland lakes were surveyed to quantify the within-and between-community changes along gradients of habitat complexity and abundance of introduced species, specifically brown trout (Salmo trutta) and redfin perch (Perca fluviatilis). Stable isotope analyses identified that trophic diversity increased with habitat complexity and abundance of native eels (Anguilla spp.) but was unaffected by introduced species. Within each community, only perch exhibited distinct dietary shifts along all environmental gradients, whereas trout and the native fishes had consistent, generalist diets. When supported with length-weight regressions, these impacts became increasingly size-dependent. For example, among the native fishes, the larger eels were unaffected by habitat, and achieved greater body condition with increased numbers of eels and perch, although more trout were detrimental to eel body condition. In contrast, the smaller-bodied natives, including elvers, all had improved body condition from increased habitat complexity and reduced numbers of trout and perch. For the introduced species, perch weights were consistent regardless of the local environment due to their variable diet, but weights of larger trout generally increased with reduced habitat complexity and greater numbers of introduced fish, although high eel densities were detrimental. Overall, our results highlight how the responses to environmental stressors, even in depauperate communities, are complicated and generally species-specific. Nonetheless, it was habitat degradation that had the most wide-ranging negative impacts on native fishes, with perch numbers only affecting the smaller-bodied natives, and trout only affecting one native species. We conclude that focusing on habitat restoration in conservation strategies will provide the most efficient and effective use of resources, though the realised benefits to native species will be limited if introduced species are overly abundant.